The paradox of contemporary labour process theory. the rediscovery of labour and the disappearance of collectivism. Miguel Martinez Lucio and Paul Stewart - Stewart, Paul
Hace un análisis sobre un modelo de empresa y las estructuras ideológicas y en la capacidad organizativa